Maslahah and Justice in Islamic Inheritance: A Normative and Jurisprudential Inquiry - Munawaroh, Hifdhotul; Akmal, Haerul; Diana, Rashda; Kurniawan, Cecep Soleh (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2025)
Provisions in the transfer of property from people who died to those who were left behind, by the Fuqaha' are named as al-faraid, and or in Indonesia it is better known as Islamic inheritance law. The concept of justice in the distribution of inheritance is still a topic of discussion among the public. The zahir provisions of the Koranic texts that give men a larger share of inheritance than women and ignore equality pose a complicated problem faced by Muslims in various countries. This is because of the invisible Maslahah that is obtained by each heir. This study aims to analyze the concept of benefit in justice contained in Islamic inheritance law to answer contradictory arguments in determining benefit in the form of justice in Islamic inheritance law. This research is a literature review/research with documentation as a data collection method. Philosophical and normative approaches are being used in analyzing data, especially Islamic legal norms which are sourced from the Koran and Hadith. The results of this study indicate that in the distribution of inheritance, Islam is very concerned and even prioritizes the principles of Maslahah and justice for each heir. There is no assumption that Islamic inheritance law does not apply fairly and leads to discrimination against women, because justice has been proven on the side of benefit in the practice of dividing Islamic inheritance.